Resources, key traits and the size of fungal epidemics in Daphnia populations. (21st March 2015) - Civitello, David J.; Penczykowski, Rachel M.; Smith, Aimee N.; Shocket, Marta S.; Duffy, Meghan A.; Hall, Spencer R.; Plaistow, Stewart
Summary Parasites can profoundly affect host populations and ecological communities. Thus, it remains critical to identify mechanisms that drive variation in epidemics. Resource availability can drive epidemics via traits of hosts and parasites that govern disease spread. Here, we map resource–trait–epidemic connections to explain variation in fungal outbreaks (Metschnikowia bicuspidata) in a zooplankton host (Daphnia dentifera) among lakes. We predicted epidemics would grow larger in lakes with more phytoplankton via three energetic mechanisms. First, resources should stimulate Daphnia reproduction, potentially elevating host density. Secondly, resources should boost body size of hosts, enhancing exposure to environmentally distributed propagules through size‐dependent feeding. Thirdly, resources should fuel parasite reproduction within hosts. To test these predictions, we sampled 12 natural epidemics and tracked edible algae, fungal infection prevalence, body size, fecundity and density of hosts, as well as within‐host parasite loads. Epidemics grew larger in lakes with more algal resources. Structural equation modelling revealed that resource availability stimulated all three traits (host fecundity, host size and parasite load). However, only parasite load connected resources to epidemic size. Epidemics grew larger in more dense Daphnia populations, but host density was unrelated to host fecundity (thus breaking its link to resources). Thus, via energetic mechanisms, resource availability can stimulate key trait(s) governing epidemics in nature. A synthetic focus on resources and resource–trait links could yield powerful insights into epidemics.